2013
DOI: 10.1007/s00296-013-2909-7
|View full text |Cite
|
Sign up to set email alerts
|

Do patients with juvenile idiopathic arthritis in remission exhibit active synovitis on joint ultrasound?

Abstract: The aim of the study was to assess the presence and characteristics of subclinical synovitis using power Doppler (PD) ultrasonography on patients with juvenile idiopathic arthritis (JIA) in clinical remission and compare the findings with those of healthy children. A cross-sectional study was carried out involving the clinical (physical exam, functional capacity and laboratory tests) and ultrasonography evaluation of 34 joints (synovial fluid/hypertrophy, PD signal and bone erosion). Subclinical synovitis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…(6, 8, 11) With regard to imaging, studies have shown that MRI and ultrasound can detect subclinical arthritis in children with JIA in clinical remission. (2022) However, the clinical and prognostic significance of such findings remains unclear. (23, 24) Perhaps this uncertainty helps explain why more than half of respondents seldom or never use imaging to guide decisions on withdrawing therapy.…”
Section: Discussionmentioning
confidence: 99%
“…(6, 8, 11) With regard to imaging, studies have shown that MRI and ultrasound can detect subclinical arthritis in children with JIA in clinical remission. (2022) However, the clinical and prognostic significance of such findings remains unclear. (23, 24) Perhaps this uncertainty helps explain why more than half of respondents seldom or never use imaging to guide decisions on withdrawing therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Erosions are less common in patients with JIA than in patients with rheumatoid arthritis (18). Erosions are commonly associated with more aggressive disease, a worse prognosis, positive rheumatoid factor test results, and polyarticular over oligoarticular subtypes (34,42). The location of JIA-induced erosions depends on the patient's age; older children (mean age, 14.4 years) tend to present with marginal erosions and younger children (mean age, 8.7 years) with epiphyseal erosions (16).…”
Section: Bone Changesmentioning
confidence: 99%
“…For example, up to 36% of healthy children have "abnormalities" in one joint, including joint effusion, synovial thickening, and tenosynovitis (46). Conversely, substantial numbers of JIA patients who fulfill the clinical criteria for remission present with asymptomatic joint effusion, synovial thickening, tenosynovitis, and/ or increased vascularity (23,42,(46)(47)(48), although only 29%-39% of them progress to active disease at 6-month to 2-year follow-up (22,25,46). Interestingly, the rate of synovial hyperplasia, joint effusion, and tenosynovitis is comparable between patients with continued remission and patients with synovitis flare, while the rate of positive power Doppler signal is greater in patients with continued remission (46).…”
Section: Enthesopathymentioning
confidence: 99%
“…It has been recently argued that remission of JIA defined on clinical grounds does not couple with remission defined with imaging [ 32 34 ]. However, the clinical significance and prognostic value of this finding is unclear, as the presence of MSUS abnormalities, including PD signal, in patients with clinically defined inactive disease did not predict subsequent synovitis flare [ 35 ].…”
Section: Introductionmentioning
confidence: 99%